ORION Space for the combat of COVID-19 - Paudel, Saurav; Thapa, Jiten; Dhusu, Rajesh; Prajapati, Rakesh Chandra (Applied Science and Technology Annals, 2020)
This report discusses on background of the organization and the work it has been doing to fight against the COVID -19. Due to sudden outbreak of COVID-19, individuals and organizations from the diverse fields fromaround the world are working together to fight against the disease. ORION Space is an organization established to promote space technology in Nepal. Due to the sudden outbreak, ORION Space has also proposed an idea to develop an Automatic Cardiopulmonary Resuscitation (CPR) machine to provide some innovative solution to fight against current outbreak. CPR is a machine which can be used as an emergency procedure when the heart stops beating. CPR is the first step in treating victims of sudden cardiac arrest.